Analisis Respon Guru Dan Siswa Terhadap Pengembangan Bahan Ajar Fisika Berbasis Model POE2WE Berbantuan Google Site - Adam, Nurna; Rahman, Mardia Hi; Nana, Nana; Saprudin, Saprudin; Yusuf, Dwi Sukmawati A. (Universitas Khairun, 2023)
Technological developments in the 21st century era, especially in the field of education, are increasingly important and change the way teachers view learning. One thing that supports the learning process is the use of digital-based learning media, including Google Site. Research on the development of physics teaching materials based on the POE2WE model with the help of the Google site with the aim of: 1) Developing physics teaching materials based on the POE2WE learning model with the help of the Google site; and 2) analyze teacher and student responses to physics teaching materials based on the POE2WE learning model assisted by Google Site. The research was carried out at Madrasah Aliyah Negeri 1 (MAN 1) Tidore Islands. The research data was obtained from validation results from several validators, namely material, language and media validators used to state the suitability of teaching materials, while teacher and student responses were obtained through the results of filling out questionnaires. The data obtained from the research results showed that on average the teaching materials developed were declared very suitable for use by class XII students at MAN 1 Tidore Islands, especially regarding electromagnetic induction material. The feasibility of the teaching materials developed is 88.25%. Analysis of teacher response data obtained a result of 95.33% and for student responses a result of 96% was obtained. It can be concluded that the physics teaching materials based on the POE2WE model assisted by the Google site received a response in the category of strongly agreeing to be used.